Managing obstruction of the central airways - Williamson, J.; Phillips, M.; Hillman, D.; Eastwood, Peter (Blackwell Publishing, 2010)
Lung cancer is the most common cause of cancer death in Australia, Europe and the USA. Up to 20-30% of these cancers eventually affect the central airways and result in reduced quality of life, dyspnoea, haemoptysis, post-obstructive pneumonia and ultimately death. Non-malignant processes may also lead to central airway obstruction and can have similar symptoms. With the development of newer technologies, the last 20 years have seen the emergence of the field of interventional pulmonology to deal specifically with the diagnosis and management of thoracic malignancy, including obstruction of the central airways. This review discusses the pathology, pre-procedure work-up and management options for obstructing central airway lesions. Several treatment modalities exist for dealing with endobronchial pathology with local availability and expertise guiding choice of treatment. While the literature lacks large, multicentre, randomized studies defining the optimal management strategy for a given problem, there is growing evidence from numerous case studies of improved physiology, of quality of life and possibly of survival with modern interventional techniques. © 2010 Royal Australasian College of Physicians.